Inner ear cell therapy targeting hereditary deafness by activation of stem cell homing factors - Kamiya, Kazusaku (Frontiers in Pharmacology, 2015)
Congenital deafness affects about 1 in 1000 children and more than half of them have a genetic background such as Connexin26 (CX26) gene mutation. Inner ear cell therapy for sensorineural hearing loss has been expected to be an effective therapy for hereditary deafness. Previously, we developed a novel strategy for inner ear cell therapy using bone marrow mesenchymal stem cells (MSC) as a supplement for cochlear fibrocytes functioning for cochlear ion transport. For cell therapy targeting hereditary deafness, a more effective cell delivery system to induce the stem cells into cochlear tissue is required, because gene mutations affect all cochlear cells cochlear cells expressing genes such as GJB2 encoding CX26. Stem cell homing is one of the crucial mechanisms to be activated for efficient cell delivery to the cochlear tissue. In our study, MCP-1 (monocyte chemotactic protein-1), SDF-1 (stromal cell-derived factor-1) and their receptors were found to be a key regulator for stem cell recruitment to the cochlear tissue. Thus, the activation of stem cell homing may be an efficient strategy for hearing recovery in hereditary deafness.